The audio description of sex scenes in Élite - Margherita Dore; Fabio Ciambella (Translation and Interpreting : the International Journal of Translation and Interpreting Research)
The literature regarding the Audio Description (AD) of sex-related scenes appears to be quite limited. For instance, Fryer (2016) devoted a full chapter of her monograph to issues relatingto AD and censorship, whereas, more recently, Rojo López et al. (2021) carried out an experiment on the reception of audio-described sex scenes by visually impaired participants. From a comparative standpoint, significant research was carried out by Sanderson (2009), who compared the English and Spanish ADs of sex scenes,and Sanz-Moreno (2017, 2018), who examined taboo language in a corpus of films audio described in English and Spanish. Sex has become an important feature of many films as well as a concern and central topic in many teen dramas streamed online (e.g. Sex Education, Baby, Sex/Life, to mention a few). Besides, sex scenes and strong language are normally allowed in this audiovisual content as it is not subject to the traditional TV watershed. Hence, we chose to analyse and compare the Spanish and English ADs of Season 6 of the Spanish TV series to determine how sex scenes have been handled. The comparative analysis offers insights into the challenges that the AD of this taboo topic poses, and how they are dealt with in different cultures and languages.